ANALISIS DIPLOMASI BUDAYA INDONESIA DALAM INTERNASIONALISASI BAHASA INDONESIA MELALUI BAHASA INDONESIA BAGI PENUTUR ASING (BIPA) DI THAILAND PADA TAHUN 2016 – 2019 - Indah Zaitun Sari; Umi Oktyari Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
One of the language internationalization efforts carried out by Indonesia is through the Bahasa Indonesia bagi Penutur Asing/ Indonesian Language for Foreign Speakers (BIPA) Program that is specially intended for foreign societies. One of BIPA’s target is the foreign citizen in South East Asian Region, one of the intended country is Thailand. This research analyze how internationalization of Indonesian Language through BIPA in Thailand. The process in promoting Indonesian Language did through art performance, food and batik bazaar, festival, educational cooperation. BIPA become an effective way to convey the Indonesian Language and also Indonesian culture in Thailand. The perspective that is being used in this research is the Constructivism Perspective and Cultural Diplomacy Theory. The use of these Perspective and Theory are in line with the global development that is being more advanced from time to time in all aspects, and this research is analyzing the Soft Power effort that is being carried out by Indonesian Government through BIPA focused in Thailand. This qualitative research collected the primary and secondary data. The primary data get by online interview with Indonesian Language teacher in Thailand, Afwin Sulistiawati, M.Hum. The secondary data get by journal, book,e-book, article, thesis, youtube, and website. The result of this research shows some problems in learning standard, communication, and infrastructure. The effort to spread the Indonesian Language through BIPA in Thailand is not operated is it was expected to be due to the language barrier between the teachers and the students. However, through the cultural approach (the exposure of Indonesian traditional Arts, Crafts and Foods) has been positively responded by the intended Thai citizen. Keywords: BIPA, Indonesian Culture, Cultural Diplomacy, Language Internationalization.